Extraction And Characterization Of Collagen And Development Of Value - Added Food Product By Blending With Fresh Cheese - Das, Aurobinda; Nayak, Yashaswi; Dash, Supriya (Journal of Neonatal Surgery, 2025)
Despite its reputation as a useless byproduct, fish viscera has been shown to be rich in useful proteins, peptides, and amino acids. In this research, we explore the potential of Labeorohita fish visceral hydrolysate in the food, pharmaceutical, and other product manufacturing sectors. Enzymatic hydrolysis with alcalase and protease enzymes was used to produce the hydrolysate. Protein and antioxidant activity were both elevated in the resultant hydrolysate. The hydrolysate was used into food products as a functional component to improve their nutritional profile. It was also discovered that the hydrolysate possessed antibacterial qualities, meaning it might be used as a natural preservative in foods. Hydrolysate was evaluated for its potential as a wound healer and anticoagulant by the pharmaceutical sector. The findings suggested that the hydrolysate might be utilised as a natural anticoagulant and also had a substantial impact on wound healing. Hydrolysate of Labeorohita fish viscera has promising uses in the food, pharmaceutical, and other industries due to its high concentration of bioactive chemicals.